Barriers to development: pushing the boundaries - Rodolfo A. Neirotti (Brazilian Journal of Cardiovascular Surgery, 2015)
Why some countries have failed to create democracy, wealth and happiness for their people is one of the great questions of our time. This essay encompasses a description of the multiple barriers to development that may have different characteristics, according to the context and the social structures that maintain these conditions. It would be arrogant to pretend to have all the solutions for these problems.